2009
DOI: 10.1111/j.1600-0404.1979.tb02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte transformation in the presence of myelin basic protein in multiple sclerosis and control subjects

Abstract: The transformation of lymphocytes in vitro in the presence of human myelin basic protein has been investigated in normal people, patients with multiple sclerosis (MS) and controls with other neurological diseases. There was little or no response at low concentrations (1-10 pg/ml) but significant transformation at higher concentrations (100-1000 pg/ml) in all three groups. There was no significant difference among the groups as a whole, but those MS patients who had had disease for more than 10 years did show g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…This study has confirmed our previous finding that lymphocytes from patients with acute relapses of MS do not show enhanced transformation in the presence of normal human myelin basic protein ( Hughes et al 1979). We then reviewed the conflicting evidence available in the literature.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This study has confirmed our previous finding that lymphocytes from patients with acute relapses of MS do not show enhanced transformation in the presence of normal human myelin basic protein ( Hughes et al 1979). We then reviewed the conflicting evidence available in the literature.…”
Section: Discussionsupporting
confidence: 86%
“…The transformation of the lymphocytes from this group was sufficiently greater than that of the lymphocytes from normal controls in the presence of MS myelin basic protein and MS synaptosomes to achieve significance at the 5 % level (Figs. We previously found that patients with chronic MS had increased lymphocyte transformation in the presence of normal myelin basic protein (Hughes et al 1979). The significance of this result in the present study can be seen to be due to two of the six patients (Fig.…”
Section: Cultures W I T H Normal Brainsupporting
confidence: 71%
See 3 more Smart Citations